Informed consent in pediatric practice: problems of Ukrainian legislation and prospects for their solution - M. A. Anishchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2019)
The purpose of the work is to consider the legal regulation of informed consent in pediatric practice, identify the problems of legal regulation of the above social relations, and determine the prospects for their solution.